Application of GIS Technology for Landslide Prone Area Analysis in Ambon Island, Indonesia - Rakuasa, Heinrich; Budnikov, Viktor Vladimirovich; Latue, Philia Christi (PT. Pubsains Nur Cendekia, 2025)
The application of Geographic Information System (GIS) technology in analyzing landslide-prone areas in Ambon Island, Indonesia, is becoming increasingly important given the hilly geographical conditions of Ambon Island and its slopes, making landslides a frequent occurrence. This study used slope, soil type, rainfall, and land cover variables. This research used the Storie Index Method to analyze landslide prone areas in Ambon Island. The results showed that Ambon Island has a medium vulnerability level of 38,282.53 ha, a high class of 23,922.00 ha, and a low landslide prone level with an area of 21,676.08 ha. The results of this study are expected to be used as a policy recommendation for future landslide mitigation in Ambon Island.